2017
DOI: 10.1002/nau.23309
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of clinical trials evaluating pharmacotherapy for overactive bladder in elderly patients: An assessment of trial quality

Abstract: Despite the prevalence of OAB among older age individuals, relatively few RCTs evaluate OAB treatments explicitly among elderly subjects. The findings from this quality assessment suggest some areas for improvement in both conduct and reporting of future RCTs assessing OAB treatment in elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…[22, 23] The EPHPP allows for the evaluation of internal (study design, confounding, blinding, withdrawals and dropouts, intervention integrity, analyses) as well as external (data collection methods, selection bias) validity of studies. [24] The quality assessment results are summarised in the S1 Table.…”
Section: Literature Search Strategymentioning
confidence: 99%
“…[22, 23] The EPHPP allows for the evaluation of internal (study design, confounding, blinding, withdrawals and dropouts, intervention integrity, analyses) as well as external (data collection methods, selection bias) validity of studies. [24] The quality assessment results are summarised in the S1 Table.…”
Section: Literature Search Strategymentioning
confidence: 99%
“…The study found a significant research gap for antimuscarinics and mirabegron time-to-effect for OAB through its clinical use had been extensively researched (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Our research of the available limited data found that for these drugs, the time-toeffect was after seven days, but more investigation is needed to analyze this occurrence, especially in the first week of medication.…”
Section: Discussionmentioning
confidence: 91%
“…After that, the gather publications were reviewed manually, and the most related ones had their references checked to find other correlated publications that would be important for the study. Besides, the study chose to view currently available meta-analyses and systematic reviews that focused on pharmacotherapy of OAB to increase the data availability and validity of the research (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The older patient population with OAB has high levels of concomitant medication use and comorbidity, is more likely to experience falls and fractures, and is at increased risk of impairment of activities of daily living [6][7][8]. However, frail elderly patients with multiple comorbidities are often excluded from clinical trials [9][10][11].…”
Section: Introductionmentioning
confidence: 99%